Spectroscopic investigation of the VO2+/hyaluronate interaction - Williams, Patricia Ana María (2011)
An oxovanadium(IV) complex was prepared by interaction of aqueous solutions of VOSO4×5H2O and sodium hyaluronate, at controlled pH-values, under nitrogen atmosphere, and subsequent precipitation with absolute ethanol. The complex formation and the characteristics of the VO2+/hyaluronate interactions were confirmed by vibrational (IR and Raman) and UV-vis electronic absorption spectroscopy. Only the carboxylate groups of the glucuronic acid moiety of the polymer are involved in coordination, acting as monodentate ligands. The suggested coordination is similar to that found in the analogous Cu(II), Mn(II) and Ni(II) complexes.